Validity and Reliability of the 6-Minute Step Test in Healthy Individuals: A Cross-sectional Study. Issue 1 (January 2016) - Arcuri, Juliano F.; Borghi-Silva, Audrey; Labadessa, Ivana G.; Sentanin, Anna C.; Candolo, Cecília; Pires Di Lorenzo, Valéria A.
Abstract : Objective: To determine the 6-minute step test's (6MST) reliability and validity and to establish reference performance values of this test. Design: Prospective observational cross-sectional study. Setting: Spirometry and Respiratory Physiotherapy Laboratory, Federal University of São Carlos (institutional). Participants: Ninety-one individuals [42 men and 49 women, mean age = 39 years (SD, 17 years)] without any diagnosed diseases and with normal exercise capacity [6-minute walk test (6MWT) >75% of the predicted normal]. Independent Variables: Participants underwent two 6MST on 1 day and two 6MWT on another day in randomized order. Furthermore, age, gender, height, weight, lower limbs length, abdominal circumference, percentage of body fat, and fat-free mass were obtained. Main Outcome Measures: Test–retest reliability was assessed by comparing the findings of the two 6MST using the intraclass correlation coefficient (ICC) and Bland–Altman plot. Validity was assessed by comparing outcomes of the 6MST to outcomes of 6MWT using the Pearson correlation coefficient. A multiple regression analysis was conducted using the stepwise method to develop an equation to predict reference values. Results: The performance (mean steps ± SD) in the first and second test was 149 ± 34 and 149 ± 36 steps, respectively, which was correlated to distance (in meters) in 6MWT (r = 0.72; P < 0.05). Six-minute step test performance was reliable (ICC = 0.9; 95% confidence interval: 0.85–0.93). The equation to predict reference values for the first 6MST was significant ( P < 0.001 and R 2 = 0.48): Performance(steps) = 174 to 1.05 × Age(years) to women and Performance(steps) = 209 to 1.05 × Age(years) to men. Conclusions: Six-minute step test is a reliable and valid test. Moreover, the number of steps may be predicted by demographic and anthropometric variables with moderate strength of prediction. Clinical Relevance: Six-minute step test is an exercise test that is easy to be conducted, more tolerable than a graded exercise test, requires fewer equipments and space, and permits better monitoring of the participants. The assessment of the reliability, validity, and reference values will provide a better interpretability for clinicians to use it, especially in primary care.